Analyzing head office and site project team responsibilities and coordination affecting project performance in work-from-home arrangement - Hnin Wai Phoo; Hadikusumo, Bonaventura H. W.; Huynh, Trung Luong; Sakul Pochanart; Loom Nam Khong Pijai (Greater Mekong subregion) Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
This study explores into the influence of responsibility and coordination practices in project management, particularly focusing on schedule management, resource management, quality management, and cost management, on project performance within construction projects in Myanmar during covid 19 in work-from-home condition. The research treats four essential facets of project management (schedule, resource, quality, and cost) as independent variables, while project performance metrics (time, cost, quality, and client satisfaction) are considered as dependent variables. Additionally, the study explores potential mediating effects on the relationship between responsibility, coordination, and project performance. Furthermore, factors impacting responsibility and coordination are examined and discussed. Regression analysis is employed to explore the associations between responsibility, coordination, and project performance. Subsequently, correlation tests are conducted to identify factors influencing responsibility and coordination. Mediation analysis is performed using the PROCESS method by Hayes. The dataset is derived from 80 respondents holding positions such as project directors, deputy project directors, project managers, construction managers, and senior planning engineers in Myanmar contractor firms, primarily engaged in private construction projects. The findings highlight that the responsibility of the project cost management group exerts a substantial impact on project performance, particularly in the context of work from-home conditions in Myanmar's private construction projects. Among the project management components, cost management emerges as the most pivotal factor, with schedule management following closely as the second crucial element. Employee job motivation and commitment are identified as mediators in the relationship between both responsibilities and project performance, as well as coordination and project performance. Additionally, crucial factors influencing responsibilities and coordination activities in work-from-home settings are identified. Notably, control aspects of project management do not exhibit a significant influence on project performance in work from-home conditions. The outcomes of this research are anticipated to provide valuable insights to the construction industry for optimizing capital.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering in Construction, Engineering and Infrastructure Management, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 2023
Keywords: Flexible work arrangements; Telecommuting; Project management